Black hats, grey hairs. (Economist, 2011)
The article focuses on the incidences and effects of cybercrime throughout the world. Topics include attacks by organizations such as LulzSec and Anonymous, the arrest of internet criminals related to computer hacking, and the growth of social networks of politically-motivated hackers. The potential threats of security breaches and the effects of cloud computing on hacking are also discussed.